COMMUNICATION STRATEGIES EMPLOYED BY HIGHER EDUCATIONAL STUDENTS IN ORAL PRESENTATION OF DAYAK NGAJU LANGUAGE - Nurliana, Nurliana (JOLLT Journal of Languages and Language Teaching, 2020)
In an oral presentation of a second language, higher education students commonly face some problems in communication. To overcome these problems, communication strategies are necessary to be employed. In the speaking class of the Dayak Ngaju language course, especially in oral presentation in History of Islamic Civilization Study Program at IAIN Palangka Raya, the students employed communication strategies to overcome the problems in communication. However, most of the students tended to employ certain types of communication strategies in the oral presentation of the Dayak Ngaju language. Furthermore, there were no research reports which had been published regarding the types of communication strategies employed by the students of Dayak Ngaju language as a second language. Thus this study was intended to describe the types of communication strategies employed by the fifth-semester students of History of Islamic Civilization Study Program at IAIN Palangka Raya in oral presentation of Dayak Ngaju language. A descriptive qualitative design was employed in this study. Observation sheets, video recordings, field-notes, and interview guides are the instruments employed in this study. The results of this study showed that the students employed four of five types of communication strategies based on Celce-Murcia?s taxonomy, namely achievement or compensatory strategies, stalling or time-gaining strategies, self-monitoring strategies, and interactional strategies. The most frequent type employed was an achievement or compensatory strategies. Moreover, the most frequent subtype was code-switching.